Nicotinic acetylcholine receptors. (June 2018) - Wonnacott, Sue; Bermudez, Isabel; Millar, Neil S; Tzartos, Socrates J
Abstract : This themed section of the British Journal of Pharmacology is the product of a conference that focussed on nicotinic ACh receptors (nAChRs) that was held on the Greek island of Crete from 7 to 11 May 2017. 'Nicotinic acetylcholine receptors 2017' was the fourth in a series of triennial international meetings that have provided a regular forum for scientists working on all aspects of nAChRs to meet and to discuss new developments. In addition to many of the regular participants, each meeting has also attracted a new group of scientists working in a fast‐moving area of research. This themed section comprises both review articles and original research papers on nAChRs. Linked Articles: This article is part of a themed section on Nicotinic Acetylcholine Receptors. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.11/issuetoc /